2014
DOI: 10.1108/s0731-219920140000024006
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides and Health: A Review of Evidence on Health Effects, Valuation of Risks, and Benefit-Cost Analysis

Abstract: In this paper, we provide reviews of recent scientific findings on health effects and preference valuation of health risks related to pesticides, and the role of benefit-cost analysis in policies related to pesticides. Our reviews reveal that whereas the focus of the health literature has been on individuals with direct exposure to pesticides, e.g. farmers, the literature on preference elicitation has focused on those with indirect exposure, e.g. consumers. Our discussion of pesticides policies emphasizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 239 publications
(98 reference statements)
1
14
0
2
Order By: Relevance
“…The estimated average effect that we obtain for the exposure to pesticides in Ecuador is greater than the 30 grams found by Bozzoli and Quintana-Domeque (2014) for the effects of the collapse of the economy in Argentina in 2000-05, and also greater than the 23 grams found by Rangel and Vogl (2019) for the effect of sugar cane harvesting in Brazil. However, it is close to the 200-grams effect found for mothers that smoke (Kramer, 1987;Lindbohm et al, 2002) and to the 30-200 grams found in recent medical and environmental studies on the use of pesticides in agriculture (Rauch et al 2012;Gemmil et al, 2013;Tago et al, 2014;Larsen et al, 2017;and Mostafalou and Abdollahi, 2017).…”
Section: Introductionsupporting
confidence: 76%
“…The estimated average effect that we obtain for the exposure to pesticides in Ecuador is greater than the 30 grams found by Bozzoli and Quintana-Domeque (2014) for the effects of the collapse of the economy in Argentina in 2000-05, and also greater than the 23 grams found by Rangel and Vogl (2019) for the effect of sugar cane harvesting in Brazil. However, it is close to the 200-grams effect found for mothers that smoke (Kramer, 1987;Lindbohm et al, 2002) and to the 30-200 grams found in recent medical and environmental studies on the use of pesticides in agriculture (Rauch et al 2012;Gemmil et al, 2013;Tago et al, 2014;Larsen et al, 2017;and Mostafalou and Abdollahi, 2017).…”
Section: Introductionsupporting
confidence: 76%
“… 1 Among smallholder farms (farms with <2 ha), 2 pesticides are the dominant form of pest management. 3 These chemicals can have a negative impact on the environment 4 , 5 and human health, 6 , 7 particularly in low- and middle-income countries (LMICs) 8 , 9 and when used unintentionally. 10 LMICs often lack pesticide use regulations or implementation thereof, and have limited resources available to deal with the environmental and health consequences of pesticide use, such as access to a functioning health system or monitoring of water quality in open water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Denoting ≡ L/N > 1, we obtain c A = ( − 1)(1 − b)/b, and the land rent is positive if > 1/(1 − b), i.e., if the population is sufficiently large, a condition assumed to hold in the following: 20 The disutility term hZ encompasses impacts due to exposure to pesticides, which includes environmental impacts as well as impacts on human health through direct (farmers) or indirect (rural populations) exposure. These latter impacts are well known and appear to be the largest (Tago et al, 2014). We do not consider health impacts on consumers through pesticide residues in food that are much smaller and less documented (Winter and Davis, 2006).…”
Section: 2mentioning
confidence: 99%